PERAN GENERASI MILENIAL DALAM PENGEMBANGAN DESA WISATA DI DANAU TOBA - Rajagukguk, Tri Putra; Sofianto, Kunto (Fakultas Ilmu Budaya Universitas Mulawarman, 2020)
The Millennials are terms that include human phenomena and are often talked about in cultural themes of society. This study aims to analyse the role of millennials in the development of tourism villages in Lake Toba and its implications for the preservation of cultural identities (case studies in the village of Simangulampe). The interview form is an open, semi-structured interview. Participants selected in the collection of data through interviews are the administrators of a youth organization (millennials) and indigenous people gathered in Simangulampe tourism village so that they can provide precise information about Potential, constraints, and strategies for the development of tourism attraction in the village. This research has led to the findings that the role of millennials in Lake Toba consists of: (1) The establishment of the GEMASAKTI organization against the potential development of tourism villages. (2) Tourism village socialization by generation of millennials on the development of Tourism Village (3) Problems and constraints of millennials related to the cultures and customs affected by modernity, mindset, human resources, Infrastructure availability, and promotional activities. (4) Form of millennial innovation related to the development efforts of Simangulampe tourism village is done by training and works. The implications are that millennials can familiarize themselves with socio-cultural traditions so that the cultural identity can be preserved and tourism creations in Lake Toba are progressing.